Feeling of agency versus judgment of agency in passive movements with various delays from the stimulus - Dubynin I. A.; Shishkin S. L. (Psychology in Russia: State of Art, 2017)
Background. The sense of agency (SoA) provides us with the experience of being a physical agent with free will. On a phenomenological basis, SoA can be divided into sensory components (feeling of agency, FoA) and more cognitive components (judgment of agency, JoA). Both these components can be independently measured.